UNDERSTANDING THE SOCIAL CHANGE AND DEVELOPMENT IN THE “THIRD WORLD”: A BOOK OVERVIEW - Kinza Fatima; Mukhammad Ali Turdialiyev (Scholar Express Journals, 2021)
This paper provides a review of the book “The Globalization and Development Reader: Perspectives on Development and Global Change” written by J. Timmons Roberts, Amy Bellone Hite. It is argued that this is one of the most comprehensive works to under the social change and development in the “Third World.”
Keywords: Globalization; Third Word; Development; Constitutionalism